The impact of relative athlete characteristics on the drag reductions caused by drafting when cycling in a velodrome - Fitton, B.; Caddy, O.; Symons, D. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2018)
In competitive road and velodrome cycling, aerodynamic drag may account for more than 90% of an individual`s resistance to motion. In multiple rider events, drafting (cycling behind another athlete) can result in drag reductions for both the leading and trailing cyclists. In team events, these drag reductions can be controlled to some degree and thus, a greater understanding may benefit team performance. To investigate this, six elite female cyclists took part in a series of individual tests and 11 different team tests throughout which the sequence of the athletes was varied. The tests took place in Manchester Velodrome and were designed to mimic the team pursuit cycling event. During the experiments, the drag area of each cyclist was measured and the drag reductions were quantified. Individual drag area was found to correlate strongly with rider mass and stature but no other measured physical characteristics. The average drag reductions in positions 1-4 in the team pursuit were 4%, 42%, 48% and 47%, respectively. The variation in drag reductions correlates most strongly with relative rider mass; for example, a light cyclist following a heavy cyclist may experience 6% less drag than if the roles were reversed. Empirical models have been developed from the results which predict the drag reductions that athletes will experience from drafting based on the cyclists` relative mass.